Konstruksi Makna Pernikahan pada Kalangan Muslim Gen Z di Media Sosial: Studi Kasus Penonton Konten “Marriage is Scary” di TikTok - Rahmawati, Dina (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
Trend "Marriage is Scary" has influenced Generation Z Muslims by presenting narratives of fear and doubt about marriage on social media. This study aims to understand how Gen Z Muslims construct the meaning of this trend using Berger and Luckmann's social construction theory through in-depth interviews. The findings show that while the trend raises fears for some, the desire for marriage remains, with a stronger impact on women due to exposure to narratives of domestic violence, double burden, social pressure, and risks in marriage, whereas men remain unaffected. This research suggests the need for balanced educational media content, dialogues with parents and clerics, and pre-marital education for singles to build a positive yet realistic view of marriage. This study contributes to the literature on digital narratives and social constructions among Gen Z Muslims and highlights gendered experiences in marriage perceptions.